Non‐native Chinook salmon add nutrient subsidies and functional novelty to Patagonian streams. (27th November 2020) - Muñoz, Nicolas J.; Reid, Brian; Correa, Cristian; Neff, Bryan D.; Reynolds, John D.
Abstract: The impacts of non‐native species are hypothesised to be proportional to the functional distinctiveness of invaders in their invaded ecosystems. Throughout the Patagonia region of southern South America, Chinook salmon ( Oncorhynchus tshawytscha ) have recently established non‐native populations, and their anadromous, semelparous life cycle could be functionally unique such that marine‐derived nutrients are delivered to streams which have historically lacked such a resource linkage with the ocean. We tested the hypothesis that salmon subsidise biofilm‐associated algae in streams throughout the Aysén province of southern Chile. Using spatial and temporal variation in the presence of salmon among multiple streams and across two spawning seasons, we found strong evidence of salmon‐subsidised algae in three out of four streams examined that have spawning salmon populations. The biofilm of subsidised streams had enriched stable isotopic ratios of nitrogen and carbon, indicating that marine‐derived nutrients were incorporated by biofilms. This nutrient uptake translated into increased algal biomass and percent of total biofilm biomass composed of algae, indicating that the incorporation of marine‐derived nutrients stimulated autotrophic production of biomass. In one stream, the incorporation of marine‐derived nutrients by biofilm occurred in only one of the two studied spawning seasons. Incorporation occurred in a year with low flows of water throughout salmon spawning (4.59 m 3 /s) and did not occur in a year with much higher flows (41.6 m 3 /s), suggesting that inter‐annual variation in discharge can mediate the subsidising effect of salmon. These results indicate that Chinook salmon have bridged the historical gap between productive marine ecosystems and nutrient‐poor stream ecosystems in Patagonia. Anadromous salmon can be a significant source of nutrients in nutrient‐limited catchments, and their ongoing expansion in southern South America is likely to entail ecological impacts in stream and riparian food webs.